Flexible piezoresistive pressure sensors for smart textiles - Carvalho, Helder (2018)
The development of smart textiles relies in many applications on of textile-integrated sensors. Flexible piezoresistive pressure sensors have many potential applications, for instance in sports science. In this study, flexible pressure sensors are built using piezoresistive polymer film and conductive fabric. Tests using a universal testing machine show that the sensors are functional, accurate, although showing some hysteresis. However, methods for joining the electrode and piezoresistive layers are necessary to assure mechanical stability of the sensor, without affecting electrical contact between layers. Several methods were tested and results are reported here. The use of thermofusible bonding nets and webs has been found to be an interesting solution.